Energy Harvesting for Autonomous Wireless Sensor Networks - Vullers, Rudd J.M.; Schaijk, Rob van; Visser, Hubregt J.; Penders, Julien; Hoof, Chris Van (IEEE solid state circuits magazine, 2010)
Wireless sensor nodes (WSNs) are employed today in many different application areas, ranging from health and lifestyle to automotive, smart building, predictive maintenance (e.g., of machines and infrastructure), and active RFID tags. Currently these devices have limited lifetimes, however, since they require significant operating power. The typical power requirements of some current portable devices, including a body sensor network, are shown in Figure 1.